Socioeconomic and Psychosocial Gradients in Cardiovascular Pathogen Burden and Immune Response: The Multi-Ethnic Study of Atherosclerosis - Aiello, Allison E. (2008)
BACKGROUND: The biologic mechanisms linking socioeconomic position and psychosocial factors to cardiovascular disease (CVD) are not well understood. Immune response to persistent pathogens may be one of these mechanisms. METHODS: We analyzed cross-sectional data from the Multi-Ethnic Study of Atherosclerosis (N=999) composed of adults age 45–84. Log-binomial regression and ordinal logistic regression models were used to examine associations of socioeconomic factors and psychosocial factors with pathogen burden and immune response among those infected. Pathogen burden was assessed based on seroprevalence of Helicobacter pylori, cytomegalovirus, herpes simplex virus-1, and Chlamydia pneumoniae and antibody levels were used to characterize high immune response to all four pathogens. RESULTS: Low education was a strong and significant independent predictor of higher pathogen burden after adjustment for covariates (adjusted odds ratio (OR) 95% confidence interval (CI) 1.37, 1.19–1.57). Among subjects seropositive for all four pathogens, low education and a higher level of chronic psychosocial stress showed a positive association with higher antibody response, although associations were no longer significant in models with all covariates included (OR = 1.64, 95%CI 0.82–3.31 for lowest vs. highest educational category and OR= 1.29, 95%CI 0.96–1.73 for a one level increase in chronic stress). CONCLUSION: Pathogen burden and heightened immune response may represent a biological pathway by which low socioeconomic position and chronic stress are related to increased rates of cardiovascular disease.